Hannah Arendt y el "Animal Laborans". Reflexiones en torno a la condición humana - Saavedra, Javier (Nómadas. Critical Journal of Social and Juridical Science, 2011)
In this article I base on the Hannah Arendt’s thesis from her essay “The Human Condition” about the supremacy of the “Homo Laborans” above the “Homo Faber” and the “Man of Action” in the modern society. The world in which Hannah Arendt wrote “The Human Condition” dominated by the cold war and still an early financial capitalism shows very different characteristics to our world. Therefore, the thesis about the supremacy of the “Animal Laborans” requires to be considering in the world of the XXI century. In this article I introduce briefly the Arendt’s main thesis about the supremacy of the “Animal Laborans” and the dissolution of public spaces and privates in the “society”. Next, I point out the differences between the original “Animal Laborans” described in “The Human Condition” and the second generation “Animal Laborans” in the light of the last historic events as 11-S, the fear to terrorism or the recent credit crisis. Finally, I reflect about the need of recovering the “Man of Action” and the requirements of the politic action.
Keywords: Hanna Arendt; “The Human Condition”; “Animal Laborans”; Politic action